Free-free opacity in warm dense aluminum - Vinko, S; Gregori, G; Desjarlais, M; Nagler, B; Whitcher, T; Lee, R; Audebert, P; Wark, J (2009)
We present calculations of the free-free opacity of warm, solid-density aluminum at photon energies between the plasma frequency at 15 eV and the L-edge at 73 eV, using both density functional theory combined with molecular dynamics and a semi-analytical model in the RPA framework which includes exciton contributions. As both the ion and electron temperature is increased from room temperature to 10 eV, we see a marked increase in the opacity. The effect is less pronounced if only the electron temperature is allowed to increase, while the lattice remains at room temperature. The physical significance of these increases is discussed in terms of intense light-matter interactions on both femtosecond and picosecond time scales. © 2009 Elsevier B.V. All rights reserved.